Degradable bioactive composite bone cement and preparation process thereof
By employing a crosslinking agent preparation process using CMC, recombinant I collagen, and BCP biphasic microsphere powder, the stability and biocompatibility issues of existing bone cements have been resolved, enabling the preparation of biodegradable composite bone cements with good mechanical and osteoconductive properties. During degradation, these cements promote bone regeneration and reduce inflammation.
Patent Information
- Application Number
- CN202511094977.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-06
- Publication Date
- 2025-11-11
AI Technical Summary
Existing bone cements have problems in clinical applications, such as low strength, uncontrollable degradation, high cost, unverified safety, and complex operation, making it difficult to achieve good stability, mechanical properties, biocompatibility, and osteoconductive properties.
Bioactive composite bone cement was prepared using CMC, recombinant I collagen and BCP biphase microsphere powder as the main components, and NHS and EDC crosslinking agents were used to form a CMC-collagen-BCP ternary system. Combined with the organic-inorganic hybridization of modified polyester and BCP biphase microsphere powder, a stable three-dimensional network was constructed.
A biodegradable bone cement with good stability, mechanical properties, biocompatibility and osteoconductivity was prepared. The process is simple, injectable, and the degradation is controllable. The degradation products promote bone regeneration, reduce inflammatory response and improve bioactivity.
Smart Images

Figure CN120919422A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterials technology, specifically to a biodegradable bioactive composite bone cement and its preparation process. Background Technology
[0002] Bone cement is a type of bone repair material that is easy to handle in clinical surgery, can be shaped as needed like cement, and self-cures. It has wide applications in the repair and replacement of bone and tooth defects, as well as in plastic surgery and cosmetic procedures. Currently, the main types of bone cement produced include: calcium phosphate-based bone cement, calcium sulfate-based bone cement, functional bone cement, polymer-based bone cement, and composite bone cement. Calcium phosphate-based bone cement has low strength, slow curing, and uncontrollable degradation; calcium sulfate-based bone cement has low strength and degrades too quickly; functional bone cement is expensive, and its long-term safety needs to be verified; polymer bone cement is exothermic, non-degradable, and poses a toxic risk; composite bone cement has a complex manufacturing process, and its stability needs optimization.
[0003] Therefore, it is necessary to develop a novel high-performance composite bone cement preparation process that possesses good stability, mechanical properties, plasticity, biocompatibility, and osteoconductivity, while also exhibiting controllable degradation, simple operation, and injectability. We propose a biodegradable bioactive composite bone cement and its preparation process. Summary of the Invention
[0004] The purpose of this invention is to provide a biodegradable bioactive composite bone cement and its preparation process to solve the problems mentioned in the background art.
[0005] To address the aforementioned technical problems, the present invention provides the following technical solution: a biodegradable bioactive composite bone cement and its preparation process.
[0006] As a biodegradable bioactive composite bone cement of the present invention, it comprises the following components: CMC (carboxymethyl cellulose), recombinant I collagen, BCP biphasic microsphere powder (biphasic calcium phosphate ceramic powder) and crosslinking agent.
[0007] Furthermore, the crosslinking agent is NHS (N-hydroxysuccinimide) and EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide).
[0008] Furthermore, the bone cement comprises the following components by weight: 5-15 parts recombinant type I collagen, 0.5-5 parts CMC, 10-30 parts BCP biphasic microsphere powder, 0.5-2 parts crosslinking agent NHS, and 1-7 parts crosslinking agent EDC.
[0009] A process for preparing a biodegradable bioactive composite bone cement includes the following steps: Prepare a CMC solution, add recombinant I collagen, mix and dissolve; add BCP biphasic microsphere powder, stir evenly; finally add a crosslinking agent to obtain a mixture; react to obtain biodegradable bioactive composite bone cement.
[0010] Furthermore, the mixture comprises the following components by weight: 5wt%–15wt% recombinant type I collagen, 0.5wt%–5wt% CMC, 10wt%–30wt% BCP biphasic microsphere powder, 0.5wt%–2wt% crosslinking agent NHS, and 1wt%–7wt% crosslinking agent EDC.
[0011] Furthermore, the preparation process of the CMC solution is as follows: heat the water for injection in a water bath to 30℃~80℃, slowly add CMC, and stir magnetically until homogeneous.
[0012] Furthermore, when adding recombinant type I collagen, the water bath temperature should be adjusted to 10℃~50℃ and magnetic stirring should be used in the CMC solution. When adding BCP biphase microsphere powder, continuous magnetic stirring is required.
[0013] Furthermore, the crosslinking agent is added at a temperature of 20℃ to 40℃, mixed evenly, and solidified after reacting for 3 to 10 minutes to obtain biodegradable bioactive composite bone cement.
[0014] In the above technical solution, (1) the carboxyl group (-COO-) in carboxymethyl cellulose and the (-NH3+) in collagen form ionic bonds under the activation environment of EDC / NHS, generating electrostatic interaction, which can enhance the network stability of bone cement. (2) EDC activates the carboxyl group (-COOH) of collagen to generate an unstable O-acyl isourea intermediate; NHS reacts with the intermediate to form a stable NHS ester (Collagen-COO-NHS); then the NHS ester condenses with another amino group (-NH2) of CMC or collagen to form an amide bond (-CONH-), thus constructing a three-dimensional network of bone cement. (3) Ca2+ on the surface of BCP biphasic microsphere powder combines with -COO- of CMC to form a coordination bond, while the microspheres are dispersed in the gel network as a rigid filler. Through the chemical crosslinking and physical entanglement of the CMC-collagen-BCP ternary system, the mechanical strength of the prepared bone cement is improved, and it has good degradability, bioactivity and clinical operability. Through component and process design, a composite bone cement with good stability, mechanical properties, plasticity, biocompatibility, and osteoconductivity was prepared using recombinant type I collagen, CMC, and BCP biphasic microsphere powder as raw materials, dissolved in water for injection, and NHS and EDC as crosslinking agents. This composite cement is also biodegradable, easy to handle, and injectable. The bone cement prepared using the above process has an initial setting time of 3-10 minutes and a final setting time of 6-15 minutes.
[0015] Furthermore, the mixture also contains polypropylene fumarate, which has been modified and grafted, as detailed in the following process: Dimethylaminoethyl methacrylate was dissolved in dimethyl sulfoxide (DMSO); 4-hydroxy-1,3-propanesulfonyl lactone was slowly added, and the mixture was reacted at 35-40℃ for 24 h; the mixture was cooled and recrystallized, purified, filtered, washed, and dried under vacuum to obtain the grafted monomer. The grafted monomer and photoinitiator were dissolved in a solvent to prepare a reaction solution; polypropylene fumarate was added, and the reaction was carried out under vacuum and ultraviolet irradiation at 45-50°C for 20-30 minutes; the mixture was filtered, extracted, washed, and dried to constant weight to obtain the modified polyester.
[0016] Furthermore, the molar ratio of dimethylaminoethyl methacrylate to 4-hydroxy-1,3-propanesulfonyl lactone (CAS:10200-48-3) is 1:(1.1~1.2). The ratio of dimethylaminoethyl methacrylate to dimethyl sulfoxide is 9 g / 100 mL; 4-Hydroxy-1,3-propanesulfonyl lactone was added as a 7.8 wt% dimethyl sulfoxide solution.
[0017] Furthermore, the modified polyester comprises the following components by weight: 100 parts polypropylene fumarate, 5-10 parts grafted monomer, 0.5-1.0 parts photoinitiator, and 10-50 parts solvent. The photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), and the solvent is dimethyl sulfoxide (DMSO). The ultraviolet irradiation uses a 405nm LED light source with a light intensity of 10-15mW / cm² and an irradiation distance of 10cm.
[0018] Furthermore, polyfuric acid propylene glycol ester should be dried before use; Purification was performed using column chromatography (silica gel column, eluent: CH2Cl2 / MeOH = 10:1) to ensure that the purity of the grafted monomer was >98%. The extraction process involved washing three times with ethanol / water (V / V=7:3) to thoroughly remove unreacted monomers and initiators.
[0019] In the above technical solution, the sulfonyl lactone in 4-hydroxy-1,3-propanesulfonyl lactone undergoes ring-opening and reacts with the tertiary amine group in dimethylaminoethyl methacrylate to form an amphiphilic compound, denoted as the graft monomer. Then, under the action of a photoinitiator, the graft monomer is grafted onto the carbon-carbon double bond of polypropylene fumarate to obtain polypropylene fumarate with amphiphilic side chains, denoted as the modified polyester.
[0020] Furthermore, the modified polyester is added in the form of a composite addition with BCP biphase microsphere powder, and the specific process is as follows: Modified polyester, 2-carboxyethyl phosphoric acid, catalyst, and BCP biphase microsphere powder were blended and compounded at 120–180 °C to obtain a composite.
[0021] Furthermore, the composite comprises the following components by weight: 100 parts BCP biphase microsphere powder, 0-10 parts modified polyester, 0.5-2.0 parts 2-carboxyethyl phosphoric acid, and 0.2-0.8 parts catalyst; The catalyst is one or both of p-toluenesulfonic acid and titanate coupling agents.
[0022] Furthermore, the BCP biphase microsphere powder was vacuum dried at 120°C for 2 hours before mixing; The modified polyester was vacuum dried at 80°C for 4 hours before mixing to avoid hydrolysis side reactions. Nitrogen or argon gas is introduced during blending to prevent high-temperature oxidation.
[0023] Furthermore, before use, the BCP biphasic microsphere powder is pretreated by soaking in citric acid solution (0.1M, pH adjusted to 2.5-3.0) for 10-20 minutes, then washed, vacuum dried at 120℃ for 2 hours, and activated at 150℃ for 1 hour.
[0024] Furthermore, the composite was prepared using a torque rheometer at a speed of 30–50 rpm.
[0025] Furthermore, the composite is prepared by the following process: Take 2-carboxyethyl phosphoric acid and the catalyst p-toluenesulfonic acid, and pre-react at 80±2℃ for 1-2 min; add modified polyester, and premix at 100-120℃ for 3-5 min to obtain a premix. Under nitrogen or argon protection, the premix was mixed with BCP biphase microsphere powder using a torque rheometer and blended at 145–155 °C and 30 rpm for 10–15 min. A catalyst, titanate coupling agent, was added, and the mixture was heated to 170–180 °C and blended at 50 rpm for 15–20 min. The mixture was then cooled to room temperature, washed with ethanol, and vacuum dried at 60 °C for 12 h to obtain the composite.
[0026] Furthermore, the mass ratio of p-toluenesulfonic acid (PTSA) to titanate coupling agent (TBT) is 1:1.
[0027] In the above technical solution, the hydroxyl groups (-OH) on the surface of BCP biphase microsphere powder can form hydrogen bonds with -OPO(OH)2 in 2-carboxyethyl phosphoric acid and the hydroxyl groups in the modified polyester, thereby improving the interfacial compatibility of the prepared composite. 2-Carboxyethyl phosphoric acid (CEP) can also partially replace PO4 in the BCP biphase microsphere powder.3- An ion exchange reaction occurs, forming an organocalcium phosphate hybrid layer. Under the action of a catalyst and high temperature, the hydroxyl groups in the modified polyester undergo an esterification reaction with 2-carboxyethyl phosphoric acid, forming a covalently bonded organic-inorganic hybrid material. Through the above-mentioned hydrogen bonding, ion exchange, and covalent esterification bonding, the prepared composite exhibits enhanced interfacial bonding properties and good degradability and bioactivity.
[0028] When the prepared composite is added to the bone cement system, the sulfonic acid groups in the modified polyester form a hydrogen bond network with the polar groups (-NH2, -COOH) of CMC / collagen, effectively reducing the porosity of the system. In synergy with the stable organic-inorganic hybrid layer formed by the composite, it can effectively prevent phase separation in the system, avoid sedimentation before bone cement solidification, and improve its stability. It can also reduce the tendency of the material to brittle fracture, and help improve the overall mechanical properties and injectability of bone cement.
[0029] The phosphate ester and amphiphilic interface modifications on the surface of the composite can capture degradation products through charge adsorption, maintaining the pH of the bone cement and preventing localized acid / alkaline accumulation during degradation, thus preventing catastrophic degradation. Furthermore, it can regulate surface energy, establishing a hydrophilic-hydrophobic balance, reducing non-specific protein adsorption, activating the anti-inflammatory phenotype of macrophages, reducing fibrous encapsulation, and alleviating inflammatory responses. Simultaneously, it can mimic the sulfated glycosaminoglycan and phosphate environment of the natural bone matrix, activating osteoblasts, promoting cell adhesion, proliferation, and vascular endothelial cell migration, further enhancing the bioactivity of the prepared bone cement.
[0030] The sulfonic acid groups on the surface of the composite can interact with Ca in the bone cement through electrostatic interactions. 2+ The amino groups in collagen bind to and enhance the interfacial strength of the organic-inorganic bonds, a property that can effectively improve the compressive strength of bone cement.
[0031] Phosphate bonds are slowly hydrolyzed in the physiological environment, matching the rate of bone regeneration, and the PO4 released during degradation... 3- It can synergize with BCP biphasic microsphere powder and react with Ca in body fluids. 2+ Combined. And the sulfonic acid group is linked through Ca... 2+ Chelation induces bone-like apatite deposition, forming a carboxylated hydroxyapatite layer on the surface of bone cement, thereby enhancing the osteoconductivity of the bone cement.
[0032] The amphiphilic interface on the surface of the composite can disrupt bacterial membranes through positive charge, enhancing antibacterial effects, and repel negatively charged bacteria through negative charge, reducing bioattachment and improving antibacterial function. It can also improve the wet adhesion of bone cement, reduce surface energy, decrease device adhesion, and optimize the injectability and plasticity of bone cement.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a novel preparation process for biodegradable bioactive composite bone cement. Through component and process design, recombinant type I collagen, CMC, and BCP biphasic microsphere powder are used as raw materials, dissolved in water for injection, and NHS and EDC are used as crosslinking agents to prepare a composite bone cement with good stability, mechanical properties, plasticity, biocompatibility, and osteoconductive properties. It is also biodegradable, easy to operate, and injectable. Attached Figure Description
[0034] Figure 1 This is a picture of the finished product of the biodegradable bioactive composite bone cement prepared in Example 1; Figure 2 This is a picture of the finished product of the biodegradable bioactive composite bone cement prepared in Example 4; Figure 3 This is a microscopic image of the biodegradable bioactive composite bone cement prepared in Example 1; Figure 4 This is a picture of the finished product of the biodegradable bioactive composite bone cement prepared in Comparative Example 1. Detailed Implementation
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] In the following specific embodiments, CMC (carboxymethyl cellulose): pharmaceutical grade, purity > 99%; recombinant I collagen: purity > 99%; BCP biphasic microsphere powder (biphasic calcium phosphate ceramic powder): coprecipitation method, particle size 1-5 μm, hydroxyapatite and tricalcium phosphate mass ratio 3:2; BCP precursor powder is uncalcined BCP biphasic microsphere powder, particle size 0.5-10 μm; Polypropylene fumarate: synthesized and transesterified from fumarate bis(hydroxypropyl) diacid ester, with an average molecular weight of 1500. The ratio of dimethylaminoethyl methacrylate to dimethyl sulfoxide was 9 g / 100 mL; 4-hydroxy-1,3-propanesulfonyl lactone was added in the form of a 7.8 wt% dimethyl sulfoxide solution; purification was performed by column chromatography (silica gel column, eluent: CH2Cl2 / MeOH=10:1). Ultraviolet irradiation was performed using a 405nm LED light source with a light intensity of 12mW / cm² and a distance of 10cm; extraction was performed by washing three times with ethanol / water (V / V=7:3); The photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP); the mass ratio of the catalyst to toluenesulfonic acid and titanate coupling agent is 1:1.
[0037] Example 1: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: The water for injection was heated to 50°C in a water bath, and CMC was slowly added and magnetically stirred until homogeneous to obtain a CMC solution. The water bath temperature was adjusted to 40°C, and recombinant type I collagen was added and magnetically stirred until dissolved. BCP biphasic microsphere powder was added and stirred until homogeneous while continuing magnetic stirring. Finally, a crosslinking agent was added at a system temperature of 25°C to obtain a mixture. The mixture was allowed to set for 3 minutes to obtain a biodegradable bioactive composite bone cement. The mixture contained the following components by mass: 7wt% recombinant type I collagen, 0.8wt% CMC, 23wt% BCP biphasic microsphere powder, 0.5wt% crosslinking agent NHS, and 2wt% crosslinking agent EDC.
[0038] Example 2: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: The water for injection was heated to 70°C in a water bath, and CMC was slowly added while magnetically stirred until homogeneous to obtain a CMC solution. The water bath temperature was adjusted to 50°C, and recombinant type I collagen was added while magnetically stirring and mixed until dissolved. BCP biphasic microsphere powder was added while continuously magnetically stirring and stirred until homogeneous. Finally, a crosslinking agent was added at a system temperature of 40°C to obtain a mixture. Initial setting was achieved after 4 minutes of reaction to obtain biodegradable bioactive composite bone cement. The mixture contained the following mass components: 10wt% recombinant type I collagen, 3wt% CMC, 15wt% BCP biphasic microsphere powder, 0.5wt% crosslinking agent NHS, and 4wt% crosslinking agent EDC.
[0039] Example 3: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: The water for injection was heated to 60°C in a water bath, and CMC was slowly added and magnetically stirred until homogeneous to obtain a CMC solution. The water bath temperature was adjusted to 50°C, and recombinant type I collagen was added and magnetically stirred until dissolved. BCP biphasic microsphere powder was added and stirred until homogeneous while continuing magnetic stirring. Finally, a crosslinking agent was added at a system temperature of 40°C to obtain a mixture. The mixture was allowed to set for 6 minutes to obtain a biodegradable bioactive composite bone cement. The mixture contained the following components by mass: 15wt% recombinant type I collagen, 2.5wt% CMC, 25wt% BCP biphasic microsphere powder, 0.6wt% crosslinking agent NHS, and 5wt% crosslinking agent EDC.
[0040] Example 4: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: Step 1: Dissolve dimethylaminoethyl methacrylate in dimethyl sulfoxide; slowly add 4-hydroxy-1,3-propanesulfonyl lactone and react at 35°C for 24 h; cool and recrystallize, purify, filter, wash, and vacuum dry to obtain the grafted monomer; the molar ratio of dimethylaminoethyl methacrylate to 4-hydroxy-1,3-propanesulfonyl lactone is 1:1.1; The polypropylene fumarate was dried; the grafted monomer and photoinitiator were dissolved in a solvent to prepare a reaction solution; polypropylene fumarate was added, and the reaction was carried out under vacuum and ultraviolet irradiation at 45°C for 20 min; the mixture was filtered, extracted, washed, and dried to constant weight to obtain the modified polyester; the modified polyester consisted of the following components by mass: 100 parts polypropylene fumarate, 5 parts grafted monomer, 0.5 parts photoinitiator, and 10 parts dimethyl sulfoxide solvent; Step 2: Pretreatment of BCP biphase microsphere powder: Immerse in citric acid solution at pH 2.5 for 10 min, wash, vacuum dry at 120℃ for 2 h, and activate at 150℃ for 1 h; vacuum dry modified polyester at 80℃ for 4 h. 2-Carboxyethyl phosphoric acid and the catalyst p-toluenesulfonic acid were pre-reacted at 78℃ for 1 min; modified polyester was added and premixed at 100℃ for 3 min to obtain a premix. Under nitrogen protection, the premix was mixed with BCP biphase microsphere powder using a torque rheometer and blended at 145℃ and 30 rpm for 10 min. A catalyst, a titanate coupling agent, was added, and the mixture was heated to 170℃ and blended at 50 rpm for 20 min. After cooling to room temperature, the mixture was washed with ethanol and vacuum dried at 60℃ for 12 h to obtain the composite. The composite consisted of the following components by mass: 100 parts BCP biphase microsphere powder, 3 parts modified polyester, 0.5 parts 2-carboxyethyl phosphoric acid, and 0.2 parts catalyst. Step 3 is the same as in Example 1. The mixture includes the following components by mass: 7 wt% recombinant type I collagen, 0.8 wt% CMC, 23 wt% complex, 0.5 wt% crosslinking agent NHS and 2 wt% crosslinking agent EDC. The mixture is reacted for 3.5 min for initial setting to obtain biodegradable bioactive composite bone cement.
[0041] Example 5: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: Step 1: Dissolve dimethylaminoethyl methacrylate in dimethyl sulfoxide; slowly add 4-hydroxy-1,3-propanesulfonyl lactone and react at 38°C for 24 h; cool and recrystallize, purify, filter, wash, and vacuum dry to obtain the grafted monomer; the molar ratio of dimethylaminoethyl methacrylate to 4-hydroxy-1,3-propanesulfonyl lactone is 1:1.15; The polypropylene fumarate was dried; the grafted monomer and photoinitiator were dissolved in a solvent to prepare a reaction solution; polypropylene fumarate was added, and the reaction was carried out under vacuum and ultraviolet irradiation at 48°C for 25 min; the mixture was filtered, extracted, washed, and dried to constant weight to obtain the modified polyester; the modified polyester consisted of the following components by mass: 100 parts polypropylene fumarate, 7.5 parts grafted monomer, 0.8 parts photoinitiator, and 30 parts dimethyl sulfoxide solvent; Step 2: Immerse the BCP biphase microsphere powder in a citric acid solution with a pH of 2.7 for 15 minutes, wash it, and then vacuum dry it at 120°C for 2 hours and activate it at 150°C for 1 hour; vacuum dry the modified polyester at 80°C for 4 hours. 2-Carboxyethyl phosphoric acid and the catalyst p-toluenesulfonic acid were pre-reacted at 80℃ for 1.5 min; modified polyester was added and premixed at 10℃ for 4 min to obtain a premix. Under nitrogen protection, the premix was mixed with BCP biphase microsphere powder using a torque rheometer and blended at 150℃ and 30 rpm for 12 min. A catalyst, a titanate coupling agent, was added, and the mixture was heated to 175℃ and blended at 50 rpm for 18 min. After cooling to room temperature, the mixture was washed with ethanol and vacuum dried at 60℃ for 12 h to obtain the composite. The composite consisted of the following components by mass: 100 parts BCP biphase microsphere powder, 6 parts modified polyester, 1.2 parts 2-carboxyethyl phosphoric acid, and 0.5 parts catalyst. Step 3 is the same as in Example 1. The mixture includes the following components by mass: 7 wt% recombinant type I collagen, 0.8 wt% CMC, 23 wt% complex, 0.5 wt% crosslinking agent NHS and 2 wt% crosslinking agent EDC. The mixture is reacted for 4.2 min for initial setting to obtain biodegradable bioactive composite bone cement.
[0042] Example 6: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: Step 1: Dissolve dimethylaminoethyl methacrylate in dimethyl sulfoxide; slowly add 4-hydroxy-1,3-propanesulfonyl lactone and react at 40℃ for 24 h; cool and recrystallize, purify, filter, wash, and vacuum dry to obtain the grafted monomer; the molar ratio of dimethylaminoethyl methacrylate to 4-hydroxy-1,3-propanesulfonyl lactone is 1:1.2; The polypropylene fumarate was dried; the grafted monomer and photoinitiator were dissolved in a solvent to prepare a reaction solution; polypropylene fumarate was added, and the reaction was carried out under vacuum and ultraviolet irradiation at 50°C for 30 min; the mixture was filtered, extracted, washed, and dried to constant weight to obtain the modified polyester; the modified polyester consisted of the following components by mass: 100 parts polypropylene fumarate, 10 parts grafted monomer, 1.0 part photoinitiator, and 50 parts solvent. Step 2: Immerse the BCP biphasic microsphere powder in a citric acid solution with a pH of 3.0 for 20 minutes, wash it, and then vacuum dry it at 120°C for 2 hours and activate it at 150°C for 1 hour; vacuum dry the modified polyester at 80°C for 4 hours. 2-Carboxyethyl phosphoric acid and the catalyst p-toluenesulfonic acid were pre-reacted at 82℃ for 2 min; modified polyester was added and premixed at 120℃ for 5 min to obtain a premix. Under nitrogen protection, the premix was mixed with BCP biphase microsphere powder using a torque rheometer and blended at 155℃ and 30 rpm for 15 min. A catalyst, a titanate coupling agent, was added, and the mixture was heated to 180℃ and blended at 50 rpm for 15 min. After cooling to room temperature, the mixture was washed with ethanol and vacuum dried at 60℃ for 12 h to obtain the composite. The composite consisted of the following components by mass: 100 parts BCP biphase microsphere powder, 10 parts modified polyester, 2.0 parts 2-carboxyethyl phosphoric acid, and 0.8 parts catalyst. Step 3 is the same as in Example 1. The mixture includes the following components by mass: 7 wt% recombinant type I collagen, 0.8 wt% CMC, 23 wt% complex, 0.5 wt% crosslinking agent NHS and 2 wt% crosslinking agent EDC. The mixture is reacted for 5.0 min for initial setting to obtain biodegradable bioactive composite bone cement.
[0043] Comparative Example 1: The BCP biphasic microspheres were replaced with BCP precursor powder. The other raw materials, dosages, and preparation methods were the same as in Example 1. The mixture included the following mass components: 7 wt% recombinant type I collagen, 0.8 wt% CMC, 23 wt% BCP precursor powder, 0.5 wt% crosslinking agent NHS, and 2 wt% crosslinking agent EDC, to obtain biodegradable bioactive composite bone cement.
[0044] Comparative Example 2: The amounts of recombinant collagen and CMC were changed, while the types, amounts, and preparation methods of the other raw materials were the same as in Example 1. The mixture included the following mass components: 4 wt% recombinant type I collagen, 3.8 wt% CMC, 23 wt% BCP biphasic microsphere powder, 0.5 wt% crosslinking agent NHS, and 2 wt% crosslinking agent EDC, to obtain biodegradable bioactive composite bone cement.
[0045] Comparative Example 3: CMC was not used. The other raw materials, dosages, and preparation methods were the same as in Example 1. The mixture included the following components by mass: 7 wt% recombinant type I collagen, 23 wt% BCP biphasic microsphere powder, 0.5 wt% crosslinking agent NHS, and 2 wt% crosslinking agent EDC, to obtain biodegradable bioactive composite bone cement.
[0046] Comparative Example 4: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: Step 1: The grafting monomer is 4-[[2-(methacryloyloxy)ethyl]dimethylamino]butane-1-sulfonate (CAS: 6613-65-6); Step 2: The BCP biphase microsphere powder was not pretreated; The remaining process steps are the same as in Example 4, resulting in biodegradable bioactive composite bone cement.
[0047] Comparative Example 5: A preparation process for a biodegradable bioactive composite bone cement, comprising the following process steps: Step 1: The grafting monomer is N,N,N-trimethyl-2-[(2-methyl-2-acryloyl)oxy]ethylamine (CAS: 33611-56-2). The remaining process steps are the same as those in Comparative Example 4, resulting in biodegradable bioactive composite bone cement.
[0048] Comparative Example 6: A preparation process for a biodegradable bioactive composite bone cement, comprising the following steps: Step 1: Under nitrogen protection, 2-carboxyethyl phosphoric acid and BCP biphase microsphere powder were mixed using a torque rheometer and co-composite at 120℃ and 40rpm for 20min; cooled to room temperature, washed with ethanol, and vacuum dried at 60℃ for 12h to obtain the composite; the composite consisted of the following mass components: 100 parts BCP biphase microsphere powder and 0.5 parts 2-carboxyethyl phosphoric acid; Step 2 is the same as step 3 in Example 4. The mixture includes the following components by mass: 7 wt% recombinant type I collagen, 0.8 wt% CMC, 23 wt% complex, 0.5 wt% crosslinking agent NHS and 2 wt% crosslinking agent EDC, to obtain composite bone cement.
[0049] Comparative Example 7: A preparation process for a biodegradable bioactive composite bone cement, comprising the following process steps: The water for injection was heated to 50°C in a water bath, and CMC and polypropylene fumarate were slowly added and magnetically stirred until homogeneous to obtain a CMC solution. The water bath temperature was adjusted to 40°C, and recombinant type I collagen was added and magnetically stirred until dissolved. BCP biphasic microsphere powder was added and stirred until homogeneous. Finally, a crosslinking agent was added at a system temperature of 25°C to obtain a mixture. The mixture was allowed to set for 3 minutes to obtain a biodegradable bioactive composite bone cement. The mixture contained the following components by mass: 7wt% recombinant type I collagen, 0.8wt% CMC, 22wt% BCP biphasic microsphere powder, 1wt% polypropylene fumarate, 0.5wt% crosslinking agent NHS, and 2wt% crosslinking agent EDC.
[0050] Experiment: The composite bone cements obtained in Examples 1-6 and Comparative Examples 1-7 were tested for their properties and the results were recorded. Injectability test: Using GB / T 16886.11 as a reference standard, composite bone cement (before initial setting) was loaded into a medical syringe, and an 18G needle was used to push it outward at an extrusion rate of 10 mm / min. The maximum injection force was recorded. Plasticity test: The composite bone cement (before initial setting) was loaded into a medical syringe, and after injection, it was allowed to stand for 5 minutes. The diameter deformation rate was then measured. The initial diameter was 6 mm. Compressive strength test: Composite bone cement (before initial setting) was poured into a cylindrical mold with a diameter of 6 mm and a height of 12 mm. After solidification, the mold was removed to obtain a solidified composite bone cement sample. The sample was placed in physiological saline at 37℃ and cured at a constant temperature for 24 h. The sample was then removed and dried at room temperature for 30 min. The compressive strength of the sample was tested using a mechanical testing machine with a loading speed of 1.0 mm / min. Collapse resistance test: The composite bone cement was injected into PBS solution (pH 7.4) at 37℃ and shaken (50 rpm) for 24 h, and the mass loss rate was calculated. Bone conduction test: Using ISO 23317 as the reference standard, samples of composite bone cement after solidification were soaked in SBF at 37℃ for 7 days, and the surface Ca / P ratio was detected by SEM-EDS. Antibacterial test: Take a sample of the composite bone cement after it has solidified, and inoculate its surface with Staphylococcus aureus (1×10⁻⁶). 5 (CFU / mL), and the antibacterial rate was calculated after 24 hours; Table 1. Experimental data on injectability, plasticity, flaking resistance, mechanical properties, osteoconductivity, and antibacterial properties.
[0051] In vitro degradation test: After the composite bone cement sample has solidified, it is immersed in degradation solution (SBF) at 37℃ for 14 days to detect its mass loss and pH fluctuation range. Collapse Degradability Test: Take samples after in vitro degradation and test their anti-collapse performance again to calculate the mass loss rate; Water retention test: After the composite bone cement sample has solidified, it is soaked in physiological saline at 37℃ for 24 hours. After taking it out, the surface moisture is absorbed with filter paper, and it is vacuum dried at 60℃ to constant weight. The change in mass before and after the experiment is detected and recorded as the water retention rate. Anti-inflammatory performance test: Based on GB / T 16886.5 and ISO 10993-6, the solidified composite bone cement samples were immersed in DMEM medium (37℃, 24h) to prepare an extract (concentration 1cm² / mL); RAW264.7 macrophages were seeded in 96-well plates, and the extract was added for 24h of culture; the concentrations (pg / mL) of TNF-α and IL-6 in the supernatant were determined by ELISA. Table 2. In vitro degradability, slump-degradability, water retention, and anti-inflammatory experimental data
[0052] Based on the data in the table above, the following conclusions can be clearly drawn: The composite bone cements obtained in Examples 1-6 were compared with those obtained in Comparative Examples 1-7. The test results show that... 1. Examples 1-3 provide a preparation process for a biodegradable bioactive composite bone cement. Through component and process design, a composite bone cement with good stability, mechanical properties, plasticity, biocompatibility and osteoconductive properties is prepared. The degradation is controllable, the operation is simple and it is injectable.
[0053] Compared with Example 1, Comparative Example 1, which replaced BCP biphasic microspheres with BCP precursor powder, showed poor plasticity and could not be molded. Comparative Example 2, which reduced the amount of recombinant collagen, showed a longer coagulation time, making it difficult to mold, and also resulting in lower strength and stability. Comparative Example 3, which did not use CMC, showed poorer plasticity, lower strength, and lower water retention.
[0054] 2. Examples 4-6 provide a preparation process for a biodegradable bioactive composite bone cement. By combining modified polyester with BCP biphase microsphere powder, compared to Example 1, the processes show improved resistance to collapse, compressive strength, osteoconductivity, antibacterial rate, water retention, resistance to disintegration and collapse, and anti-inflammatory properties. The modified polyester and CMC work synergistically to achieve low injection force and high shape retention. Covalent cross-linking of the modified polyester with phosphoric acid contributes to increased strength, and a stable organic-inorganic interface promotes improved resistance to collapse. BCP pretreatment and sulfonic acid-induced mineralization bring its Ca / P ratio close to that of natural bone. The degradation rate (38-45%) is significantly lower than the comparative example (>50%), and the degradation cycle matches bone regeneration (6-12 months). The amphiphilic modification inhibits inflammatory responses and exhibits good antibacterial and anti-inflammatory performance. The hydrophilic network (CMC + sulfonic acid groups) further enhances its water retention properties.
[0055] Compared to Example 4, the grafting monomers of the complexes in Comparative Examples 4 and 5 were different; the complex in Comparative Example 6 was prepared from BCP biphase microsphere powder and 2-carboxyethyl phosphoric acid; the complex in Comparative Example 7 was a dispersion mixture of BCP biphase microsphere powder and polypropylene fumarate, and its performance data deteriorated. It can be seen that the present invention achieves excellent improvements in comprehensive properties such as injectability, mechanical properties, bioactivity, degradability, and low inflammatory response through organic-inorganic hybrid design and synergistic effects of multifunctional components.
[0056] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A preparation process for a biodegradable bioactive composite bone cement, characterized in that: The process includes the following steps: Prepare a CMC solution, add recombinant I collagen, mix and dissolve; add BCP biphasic microsphere powder, stir evenly; finally add a cross-linking agent to obtain a mixture; The reaction yields biodegradable bioactive composite bone cement.
2. The preparation process of a biodegradable bioactive composite bone cement according to claim 1, characterized in that: The crosslinking agents are NHS and EDC.
3. The preparation process of a biodegradable bioactive composite bone cement according to claim 2, characterized in that: The mixture comprises the following components by weight: 5wt%–15wt% recombinant type I collagen, 0.5wt%–5wt% CMC, 10wt%–30wt% BCP biphasic microsphere powder, 0.5wt%–2wt% crosslinking agent NHS, and 1wt%–7wt% crosslinking agent EDC.
4. The preparation process of a biodegradable bioactive composite bone cement according to claim 1, characterized in that: The mixture also contains polypropylene fumarate, which has been grafted modified, as detailed in the following process: Dimethylaminoethyl methacrylate was dissolved in dimethyl sulfoxide; 4-hydroxy-1,3-propanesulfonyl lactone was slowly added, and the mixture was reacted at 35-40°C for 24 hours to obtain the grafted monomer. The grafted monomer and photoinitiator are dissolved in a solvent, and polypropylene fumarate is added. The mixture is then subjected to ultraviolet irradiation at 45–50 °C for 20–30 min under vacuum to obtain the modified polyester.
5. The preparation process of a biodegradable bioactive composite bone cement according to claim 4, characterized in that: The modified polyester is added in the form of a composite addition with BCP biphase microsphere powder, and the specific process is as follows: Take 2-carboxyethyl phosphoric acid and the catalyst p-toluenesulfonic acid, and pre-react at 78-82℃ for 1-2 min; add modified polyester, and premix at 100-120℃ for 3-5 min to obtain a premix. Under nitrogen or argon protection, the premix was mixed with BCP biphase microsphere powder using a torque rheometer and then blended at 145–155 °C and 30 rpm for 10–15 min. A catalyst, titanate coupling agent, was added, and the mixture was then heated to 170–180 °C and blended at 50 rpm for 15–20 min to obtain the composite.
6. The preparation process of a biodegradable bioactive composite bone cement according to claim 4, characterized in that: The molar ratio of dimethylaminoethyl methacrylate to 4-hydroxy-1,3-propanesulfonyl lactone is 1:(1.1 to 1.2).
7. The preparation process of a biodegradable bioactive composite bone cement according to claim 4, characterized in that: The modified polyester comprises the following components by weight: 100 parts polypropylene fumarate, 5-10 parts grafted monomer, 0.5-1.0 parts photoinitiator, and 10-50 parts solvent.
8. The preparation process of a biodegradable bioactive composite bone cement according to claim 5, characterized in that: The composite comprises the following components by weight: 100 parts BCP biphase microsphere powder, 0-10 parts modified polyester, 0.5-2.0 parts 2-carboxyethyl phosphoric acid, and 0.2-0.8 parts catalyst.
9. The preparation process of a biodegradable bioactive composite bone cement according to claim 5, characterized in that: Before use, the BCP biphasic microsphere powder is pretreated by soaking in a citric acid solution with a pH of 2.5 to 3.0 for 10 to 20 minutes, then washed, vacuum dried at 120°C for 2 hours, and activated at 150°C for 1 hour.
10. A biodegradable bioactive composite bone cement prepared according to any one of claims 1-9.